Academic Literacy in English: A Pedagogical Proposal for the Teaching of Nominalization in an Undergraduate Program - Panza, Carolina; Gonzalez Vuletich, Laura; Picchio, Romina; Dichiara, Anabella (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
The classroom account described in this article proposes a pedagogical sequence for raising undergraduate students’ awareness of nominalization as a powerful resource to enhance their academic reading and writing skills. Academic literacy requires that students familiarize themselves with ways of expressing meanings which are particularly frequent in academic texts, but which are not often present in everyday language. Nominalization is one of the features that poses a challenge for university students both for reading and for writing science-related texts. The sequence activities were organized into stages, which gradually guide students from reading a science-popularization article to notice the presence of nominalized forms, to finally using this linguistic resource in guided writing activities. It is expected that those teaching EFL at the university level will find these activities applicable and relevant to scaffold academic literacy development.